THE EFFECT OF LOADING ON THE POWER CAPACITY OF A 1-PHASE 50 KVA DISTRIBUTION TRANSFORMER - Azis Mustofa, Denny; Darmawan, Isra' Nuur; Kholistianingsih (Journal of Electronic and Electrical Power Applications, 2025)
The Effect Of Loading On The Power Capacity Of A 1-Phase 50 Kva Distribution Transformer. The 50 kVA distribution transformer at the SNT04-109 substation plays an important role in distributing electrical energy to customers. However, increasing loads can accelerate the decline in transformer performance and lifespan. This study aims to analyze the effect of loading on transformer power capacity using a descriptive quantitative approach based on load current data from 2019 to 2023. The results show that the average nighttime load current increased from 96 A in 2019 to 131 A in 2023. Based on calculations, the actual power carried has reached 28.9 kVA or 72.2% of the maximum capacity. With an annual load growth trend of around 8.7%, it is estimated that transformers will experience overloading in the coming years. If load management or uprating is not carried out, the risk of damage and decreased operational efficiency will increase. Therefore, routine monitoring and capacity planning are essential to maintain the reliability of electricity distribution.